SOLAR FLARE DURING THE ECLIPSE OF MARCH 7 OF 1970 - RIVERA TERRAZAS, LUIS; GONZALEZ, G (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1969)
A sequence of phases of the total solar eclipse of March 7, 1970 observed with the Lyot filter at the Tonantzintla Astrophysical Observatory is presented.
BOL OBS TONAN TACUB
Keywords: SOLAR, FLARE DURING, ECLIPSE, MARCH, 1970; ASTRONOMIA Y ASTROFISICA; SISTEMA SOLAR; ECLIPSE SOLAR